2019
DOI: 10.3389/fpsyg.2019.02246
|View full text |Cite
|
Sign up to set email alerts
|

Why Is There So Much More Research on Vision Than on Any Other Sensory Modality?

Abstract: Why is there so much more research on vision than on any other sensory modality? There is a seemingly easy answer to this question: It is because vision is our most important and most complex sense. Although there are arguments in favor of this explanation, it can be challenged in two ways: by showing that the arguments regarding the importance and complexity of vision are debatable and by demonstrating that there are other aspects that need to be taken into account. Here, I argue that the explanation is debat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(147 citation statements)
references
References 80 publications
4
140
0
3
Order By: Relevance
“…However, this assumption has been challenged by various studies published in the last decade, demonstrating that detailed and durable long-term memory representations are formed as a natural product of perception. While most studies have investigated visual long-term memory (Vogt and Magnussen, 2007;Brady et al, 2008;Konkle et al, 2010;Kuhbandner et al, 2017), similar results have been obtained for auditory (Hutmacher and Kuhbandner, 2020) and haptic (Hutmacher and Kuhbandner, 2018) long-term memory (for the reasons behind the dominance of vision in research, see Hutmacher, 2019). In short, performance in these studies indicated that much more of the incoming perceptual information is stored in long-term memory than previously believed.…”
Section: Introductionsupporting
confidence: 65%
“…However, this assumption has been challenged by various studies published in the last decade, demonstrating that detailed and durable long-term memory representations are formed as a natural product of perception. While most studies have investigated visual long-term memory (Vogt and Magnussen, 2007;Brady et al, 2008;Konkle et al, 2010;Kuhbandner et al, 2017), similar results have been obtained for auditory (Hutmacher and Kuhbandner, 2020) and haptic (Hutmacher and Kuhbandner, 2018) long-term memory (for the reasons behind the dominance of vision in research, see Hutmacher, 2019). In short, performance in these studies indicated that much more of the incoming perceptual information is stored in long-term memory than previously believed.…”
Section: Introductionsupporting
confidence: 65%
“…Although studies dedicated to assessing the individual significance of olfaction have demonstrated differences between health and disease, there is a gap of knowledge with respect to the mechanisms for these differences (14)(15)(16) . This is not surprising, considering that the olfactory system still remains a "neglected sense" (1,28,29) , which is also reflected in the number of studies conducted compared to other sensory organs (30) . Moreover, the improvable management and counselling of patients with OD prior to their presentation at Smell and Taste clinics also demonstrates the need to raise awareness and literacy among the medical profession for the sense of smell (28,31) .…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of the study of attention in systems neuroscience and psychology centers on visual attention in particular (Kanwisher and Wojciulik, 2000). This may reflect the general trend in these fields to emphasis the study of visual processing over other sensory systems (Hutmacher, 2019), along with the dominant role vision plays in the primate brain.…”
Section: Sensory Attentionmentioning
confidence: 99%